Hybrid Instantaneous Wave-Free Ratio–Fractional Flow Reserve versus Fractional Flow Reserve in the Real World - Shuttleworth, Kara; Smith, Kristina; Watt, Jonathan; Smith, Jamie A. L.; Leslie, Stephen J. (Frontiers in Cardiovascular Medicine, 2017)
Background: The instantaneous wave-free ratio (iFR) is a novel method to assess the ischaemic potential of coronary artery stenoses. Clinical trial data have shown that iFR has acceptable diagnostic agreement with fractional flow reserve (FFR), the reference standard for the functional assessment of coronary stenoses. This study compares iFR measurements with FFR measurements in a real world, single centre setting. Methods and results: iFR and FFR were measured in 50 coronary artery lesions in 42 patients, with FFR ≤ 0.8 classified as functionally significant. An iFR only technique, using a treatment cut-off value iFR ≤ 0.89, provided a classification agreement of 84% with FFR ≤ 0.80. Use of a hybrid iFR-FFR technique, incorporating FFR measurement for lesions within the iFR grey zone of 0.86-0.93, would improve classification agreement with FFR to 94%, with diagnosis achieved without the need for hyperaemia in 57% patients. Conclusions: This study in a real world setting demonstrated good classification agreement between iFR and FFR. Use of a hybrid iFR-FFR technique would achieved high diagnostic accuracy whilst minimising adenosine use, compared with routine FFR.